INTELLECTUAL CAPITAL DISCLOSURE IN ITALY AN EMPIRICAL ANALYSIS - Scaltrito, Davide (Journal of Contemporary Research in Management (JCRM), 2015)
Purpose: The paper aims at assessing the level of voluntary disclosure of intellectual capital in the main companies listed on the Italian Stock Exchange. Information on intangible assets provided by companies is very important for investors due to the recent advent of the knowledge economy. In particular, in this paper, it is analysed the effect that certain determinants (leverage, firm size, auditor and ownership concentration) could have on voluntary disclosures of intellectual capital information by the Italian companies observed. In order to do this, 186 annual reports of Italian listed companies for the year 2010 were analysed. Design/methodology/approach: To assess the extent of voluntary disclosure of intellectual capital an index is created to measure it and it is used in an OLS model, as dependent variable, to understand the relationship between the above mentioned determinants and intellectual capital disclosure. In order to do this, 186 annual reports were analysed and about 6,000 items of information on their intellectual capital elements were collected. Findings: Relational capital information is the most disclosed item and size affecting positively the total amount of intellectual capital disclosure. Originality/value: The paper contributes in improving knowledge about intellectual capital disclosure analysing a wide sample of Italian listed companies and assessing intellectual capital disclosure determinants.